Growth Performance, Feeding Ecology and Prey Preference of Bagrid Catfi sh, Mystus Tengara (Hamilton, 1822) in Low Saline Polyculture Ponds of Indian Sundarbans - Asish Mondal; Jitendra Kumar Sundaray; Subhra Bikash Bhattacharyya; Deepta Chakravartty; Sufi a Zaman; Abhijit Mitra (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2017)
Growth performances, feeding ecology and prey preferences of Mystus tengara (Hamilton, 1822) reared in low saline homestead traditional polyculture ponds in Sundarbans were studied for 12 months. Mixed carp early fingerlings (4.98±0.61 cm, 1.09±0.26 g) @ 14000 nos ha-1 and wild collected mixed bagrid catfish juveniles (5.09±0.48 cm, 1.38±0.11 g) including M. tengara were stocked @ 5000 juveniles ha-1. Farm yard manure @ 200 kg ha-1 was applied monthly and household dining wastes (11.37±2.08 kg ha-1 day-1) were thrown in the ponds almost daily following traditional practice. Fishes attained 31.56±2.08 g (13.92±0.88 cm) with specific growth rate of 0.95±0.15 % day-1 and exponent value of Length-Weight Relationship (b=2.99) indicated isometric growth. Numeric order of dominance of prey groups in water were Chlorophyceae, Myxophyceae, Bacillariophyceae, Insect parts and larvae, Copepods, Rotifers and Cladoceran, Fish parts and larvae, unidentified materials and Crustacean parts. Whereas, order of dominance of prey groups in stomach were Insect parts and larvae, Copepods, Myxophyceae, Rotifers and Cladoceran, Fish parts and larvae, Bacillariophyceae, Chlorophyceae, Crustacean parts and unidentified materials. Prey electivity analysis indicated significant active selection of Insect parts and larvae (E= +0.36±0.06) and Copepods (E= +0.30±0.12). Crustacean parts, Rotifers and Cladocera and Fish parts and larvae were also positively selected but were not significant. This study reveals that M. tengara is a carnivorous fish mostly preferring Insect larvae and Copepods. M. tengara can be added in low saline polyculture ponds to improve profitability and can be considered as a biological tool for Insect control.